OPTIMASI PROSES PEMBUATAN MAKANAN BERBASIS TEKNOLOGI EKSTRUSI UNTUK MENINGKATKAN KETERSEDIAAN GIZI DAN KUALITAS ORGANOLEPTIK - Megavitry, Rissa (Fruitset Sains : Jurnal Pertanian Agroteknologi, 2024)
This research investigates the use of extrusion technology in food production to enhance nutritional quality and organoleptic aspects. Through a literature study analysis, it was found that optimizing extrusion process parameters is key to producing products with improved nutritional availability. Organoleptic quality should also be considered to maintain product appeal to consumers. While extrusion technology offers significant potential, challenges and opportunities need to be identified and addressed to realize improvements in the food industry. This research also underscores the importance of interdisciplinary collaboration and attention to sustainability aspects in the development of extrusion-based food products.